Orthobiologics in orthopedic applications: a report from the TMI Havemeyer meeting on orthobiologics - Christian Lattermann; Chilan B.G. Leite; David D. Frisbie; Theodore S. Schlegel; Larry R. Bramlage; Thomas Koch; Christopher Centeno; Laurie R. Goodrich; Brian Johnstone; Rocci Trumper; Ashlee Watts; Christopher Little; et al. (Elsevier, 2022)
Readily available and effective therapeutic approaches are increasingly required to overcome the growing demand for optimized management of musculoskeletal degenerative conditions. The use of biologic therapies has been gaining ground in the orthopedic field by showing promising results. In order to review the current status of orthobiologics and to discuss the potential risks, benefits, and challenges of their implementation, a recent expert conference hosted by the C. Wayne McIlwraith Translational Medicine Institute (TMI), and funded by the Dorothy Havemeyer Foundation was held at Colorado State University, in conjunction with the official Opening of the TMI. This review summarizes the conference findings highlighting the scientific challenges, safety concerns, and translation of orthobiologics to clinical practice.